So samomorilski napadalci res verski fanatiki? - Frank, Ana (Monitor ISH, 2005)
Are suicide attackers religious fanatics? On understanding suicide attacks. The extreme nature of the phenomenon of suicide attacks tends to reinforce the general belief that such terrible and irrational acts can only be motivated by religious fanatism. Attempts have been made, however, to provide possible explanations of this phenomenon through extensive research, especially by the scientists from the Middle East. The article presents some of the insights gained into this strange phenomenon. It sheds new light on the understanding of suicide attacks by analysing cultural, historical, and religious aspects of martyrdom, taking into account also the influence of manipulation, indoctrination, and circumstances.
Keywords: islam; samomorilski napadi; fanatizem; verski fanatizem; mučeništvo; žrtvovanje; indoktrinacija; družbena vloga